Juridical Analysis of the Roles and Responsibilities of a Notary Against Deeds that are not read before the Parties: English - Vania Bella Tumiur Rohana Boru Simorangkir; Aisyah Ayu Musyafah (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
As a public official, a Notary has a role and obligation to ensure that what is in accordance with the wishes of the parties. A notary has the obligation to read the deed to the parties and write a statement of the circumstances of the appearer when he appears before the notary along with the reasons or statement of the deed not being read in the cover of the deed which is a provision contained in the law. If there is a misunderstanding between the parties regarding the preparation of the deed and causes ambiguity over the deed made, then the strength and usefulness of the notary deed needs to be questioned and also regarding the responsibility for the role of the notary who deliberately does not read the deed before the parties. In this study the aim is to examine further the role of the Notary in deed that is not read out before the parties and regarding the validity of the deed that is not read out. The research method used in this study is normative juridical, which is statutory research. It is carried out by examining problems using regulations that are related and relevant to the problem, in this case the rules that have to do with the field of notary law, namely UUJN and the Code of Ethics. Notary Public. The results of the study are that reading the deed is an obligation that must be carried out by a notary and if the notary's deed is not read out it will cause the deed to be null and void and the strength of proof becomes a private deed.